Role of Pamidronate Disodium (Aredia) in Reducing skeletal Related Events in Patients with Metastatic Bone Disease: A pilot study - Khan, Perwez; Jameel, Abid; Zaidi, Alia (Journal of Postgraduate Medical Institute, 2011)
We present our data of 14 patients (11 male and 3 female) with metastatic bone disease who were treatement with pamidronate disodium (Aredia, Novartis) for the prevention of patholgoical fractures and for the relief of bone pain due to skeletal metastases at a dose of 60mg. intravenously, every 28 days. 06 patients had multiple myeloma, 04 patients had advanced carcinoma of the rostate, 02 patients had advanced cancer of the breast while 02 patients had metastases of unkown origin. Pamidronate was administered in a dose of 60mg as an intravenous infusion, over 2 - 3 hours every 21 days. Patients have been followed up for over 6 months. 10 / 14 (70%) poatients had a substantial relief of bone pain (25 - 50% reduction) at this dose within 20 days. Pain reduction was accompainied by improved mobility, performance and quality of life. These patients had a radiological stabilization of bone disease and no new lesions were detected radiologically. none of the patients had a pathological fracture during treatment and follow-up. Pamidronate was well tolerated and side effects were minimal (03 patients had flu like symptoms and 02 had transient fever). In conclusion pamidronate (Aredia) significantly reduces skeletal morbidity, delays the development of bone metastates and fractures, provides significant relief of bone pain, reduces the use of analgesics and is well tolerated with a good safety profile. Patients with skeletal involvement due to cancer may therefore, benefit from the use of pamidronate administered either alone or in combination with cancer chemotherapy.